O29. International comparisons of activity measurements of Tc-99m and F-18. (September 2016) - Lubbe, J.; van Rooy, M.; van Staden, M.; Simpson, B.
Abstract : Introduction: The short-lived radionuclides Tc-99m and F-18 are used in nuclear medicine for imaging purposes. Hospitals must accurately measure the activity of radiopharmaceuticals administered to patients with a radionuclide activity calibrator which is traceable to a national metrology institute via calibration sources. The International Reference System Transfer Instrument (SIRTI) was recently used by the International Bureau of Weights and Measures (BIPM) to measure the activity of Tc-99m and F-18 sources prepared at the National Metrology Institute of South Africa (NMISA). These on-site measurements were compared with those made with the calibrated NMISA ionisation chamber (IC). Through comparisons such as these, equivalence to international metrology institutes and quality of measurements are demonstrated. This presentation describes the comparison process. Materials and methods: The SIRTI is a portable NaI(Tl) well counter used for on-site measurements of short-lived radionuclides at metrology institutes. In preparation for these comparisons, Tc-99m and F-18 were standardized by NMISA via the 4 π β γ liquid scintillation coincidence counting method. The results from the primary standardizations were transferred to the NMISA IC via primary standardized liquid sources. The current produced by gamma radiation emitted from these sources was used to determine calibration factors for Tc-99m and F-18. For the SIRTI comparisons, master solutions of Tc-99m and F-18 were prepared from new batches of material. From each master solution, one source was made for measurement with the NMISA IC and three for measurement with the SIRTI. The NMISA IC and calibrated balances were used to determine the activity concentration of each master solution. Using these values, the activities of the SIRTI sources were calculated and compared to the actual SIRTI measured activities. Results: Comparison results for NMISA show agreement, within uncertainties, with the international reference values previously established for Tc-99m and F-18. Conclusion: Good results from both comparisons ensure the quality of measurements and services provided via the NMISA IC for Tc-99m and F-18.